Investigating Some Neuromuscular Risk Factors of ACL Injury in Athletes with Ankle Pronation Deformity - noorollah javdaneh; hooman Minoonejad; elham shirzad (Sport Sciences and Health Research)
athletes. Researches show that pronation of ankle affects the incidence of anterior cruciate ligament (ACL) injury but no researches have been conducted on neuromuscular control related to ACL injury in athletes with increased pronation of ankle. Therefore, the aim of this study was to investigate some neuromuscular risk factors of ACL injury in athletes with ankle pronation deformity. 15 athletes with increased pronation of ankle and 15 normal athletes were purposively selected as the ample of the study. Electromyographic signals were recorded with surface electrode from four muscles (gluteus medius, lateral hamstring, vastus lateralis and soleus). MANOVA results showed a significant difference between the two groups in feed forward phase of gluteus medius (P=0.029) and biceps femoris (P=0.001) and in feedback phase of gluteus medius (P=0.005) although there were no significant differences in feed forward and feedback activities of vastus lateralis and soleus between the two groups (P≥0.05). So pronation of ankle can be a risk factor in ACL injury incidence through a change in neuromuscular function of gluteus medius and lateral hamstring muscles.